PENINGKATAN KEMAMPUAN MENULIS TEKS CERITA MORAL DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI PADA SISWA KELAS VIII.2 DI SMPN 2 RAMBAH - Yatimah Yatimah (JURNAL PENDIDIKAN ROKANIA, 2019)
This study aims to improve the learning outcomes of Indonesian language about the material of writing moral text stories by using picture media in grade VIII.2 students of SMP Negeri 2, Rambah, Rokan Hulu, Riau. The subjects of this study were students of class VIII.2 of SMP Negeri 1, totaling 30 students. The action research was carried out in 2 cycles. Data collection in this study uses the test and observation methods. Research data about the material to write moral story texts were analyzed in quantitative descriptive. The results showed that learning by using serial images media could improve Indonesian learning outcomes in the material to write moral story text in class VIII.2 of SMP Negeri 1, which in the initial condition results before being given an average rating of 63.16. In the first cycle by using serial media there was an increase so that the average grade of the class was 70.01. In the second cycle showed an increase with an average of 86.67. Based on research on improving the ability to write moral story text using serial media in class VIII.2 students of SMPN 2 Rambah, it is recommended that Indonesian teachers use serial media in learning to write moral story text and carry out learning that motivates students to be active and feel happy in participating in learning Indonesian, one of which is by using serial media